Molecular Networks in Dynamic Multilevel Systems - Orrillo, Alfredo Gastón (2018)
Dynamic multilevel systems can be assembled from molecular building blocks through two or more reversible reactions that form covalent bonds. Molecular networks of dynamic multilevel systems can exhibit different connectivities between nodes. The design and creation of molecular networks in multilevel systems require control of the crossed reactivity of the functional groups (how to connect nodes) and the conditions of the reactions (when to connect nodes). In recent years, the combination of orthogonal and communicating reactions, which can be simultaneous or individually activated, has produced a variety of systems that have given rise to macrocycles and cages, as well as molecular motors and multicomponent architectures on surfaces. A given set of reactions can lead to systems with unique responsiveness, compositions, and functions as a result of the relative reactivities. In this Concept article, different molecular networks from synthetic systems that can be produced by combinations of different reaction types are discussed. Moreover, applications of this chemistry are highlighted, and future perspectives are envisioned.